140 FAMILY DEMENTIA SUPPORT TRAINING—AN INTEGRATED CARE APPROACH. (18th November 2021) - McHale, C; Fallon, A; Donnelly, M; Dookhy, J; McGuinn, C; Domsa, M; McNally, D; Tobin, F; Kennelly, S
Abstract: Background: There are approximately 64, 000 people living with a diagnosis of dementia in Ireland. This number is expected to double to 150, 000 by 2045. The growing need for post diagnostic support has been accentuated by the fact that we are living through an unprecedented Pandemic. Our Dementia Training Network identified the need for a localised educational resource for families supporting those diagnosed with dementia across our service. Methods: Following a successful pilot in association with the Alzheimer's Society of Ireland, staff from the Specialist Memory Service, Integrated Care Team, and Primary Care created a service-informed 6 week course aimed at supporting families. A focus group preceded the first course to establish preferred content. The course delivered education on Dementia; Post Diagnostic Steps; Communication; Non cognitive symptoms; Nutrition & hydration; Assistive Technology; Forward planning and Self-care. The multi-dimensional nature of staff delivering the course creates a rich tapestry of advice and information. All staff involved work together to identify, refer and support families living with dementia in the local area. The group takes place in an accessible location and time which accommodates families. Each course attendee completes a questionnaire prior to and after commencing the group. The level of satisfaction will be measured following every course. Results: By the end of 2021, the group will have delivered education and support to 36 families. The automatic referral of all families to this resource will assist in building up confidence to support and enhance self-care. The combined participants from the catchment area will become a network of families joined together on their journey. Conclusion: This innovative service collaboration enhances the integrated nature of the Post Diagnostic Care pathway. The Integrated care approach has served to enrich the programme and allow for timely support and advice regarding localised supports.